2018
DOI: 10.1177/1060028017754225
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Toxicology of Yew Poisoning

Abstract: Most nonintentional ingestions of yew plant constituents are asymptomatic and require little intervention. Severe poisoning can result in life-threatening cardiac toxicity and require aggressive supportive care. Therapeutic interventions, such as sodium bicarbonate, digoxin immune fab, and hemodialysis that have been utilized in case studies and case series in the literature have little proven benefit. Extracorporeal life support should be considered in severe yew poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Along with gastroscopy and charcoal administration, multiple measures are used to limit the toxicity of T. baccata. 2 A particular problem is the poor response of associated arrhythmias and cardiogenic shock to atropine, 5,13 external/internal pacing 14,15 or catecholamines, 5,7,13 intravenous administration of lidocaine, 16 and sodium bicarbonate 17,18 . Few case reports attribute beneficial effects to digoxin‐specific antibodies (fab fragment) 5,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with gastroscopy and charcoal administration, multiple measures are used to limit the toxicity of T. baccata. 2 A particular problem is the poor response of associated arrhythmias and cardiogenic shock to atropine, 5,13 external/internal pacing 14,15 or catecholamines, 5,7,13 intravenous administration of lidocaine, 16 and sodium bicarbonate 17,18 . Few case reports attribute beneficial effects to digoxin‐specific antibodies (fab fragment) 5,19 .…”
Section: Discussionmentioning
confidence: 99%
“…T. baccata poisoning is observed after accidental ingestion or attempted suicide. Clinical symptoms are caused by the blockade of cellular sodium and calcium channels and range from mild gastrointestinal symptoms to seizures, cardiac dysrhythmias, and cardiogenic shock 1,2 . Confirmation of Taxine B, 3,5‐dimethoxyphenol (3,5‐DMP), or other taxines in the blood serve as markers of ingestion 3 …”
Section: Introductionmentioning
confidence: 99%
“…Mechanical cardiac support like extracorporeal membrane oxygenation may be considered if other measures have failed. Diagnosis of taxine poisoning in livestock after accidental feedings of yew bush clippings has been contingent on history of exposure and identification of yew in the digestive tract [7]. Due to their prolonged gastric transit time, yew leaf recovery from the stomach may reduce taxine absorption 3 .Our discovery of needlelike green objects consistent with the leaves of Taxus baccata in postmortem gastric contents (Figure 2) is the first reported instance of yew identification in the gastrointestinal tract of a human victim [6].…”
Section: Discussionmentioning
confidence: 98%
“…The reports described clinical manifestations similar to those observed with digoxin toxicity, including bradycardia, atrioventricular block, nausea, vomiting, abdominal pain, and hyperkalemia. Literature reports have described successful use of digoxin immune fab in managing non-digoxin cardiac glycoside poisonings with oleander leaves [24], toad venom [25], and some Chinese herbal supplements [26,27]; others have reported unfavorable outcomes, including in cases of severe yew poisoning [28,29]. b DigiFab administered following ingestion of Almendra quema grasa (n = 1), Cerbera odollam seeds (n = 3), Convallaria majalis (n = 1), Crataegus mexcicana (n = 1), Taxus baccata (English yew or European yew) (n = 2), Jamaican stone (n = 1), oleander leaves (n = 1), Piedra China (n = 1), or toad head (n = 1) An important strength of our study is the national representation of AEs reported for DigiBind and DigiFab in the real-world setting, during a postmarketing study period of more than 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…The reports described clinical manifestations similar to those observed with digoxin toxicity, including bradycardia, atrioventricular block, nausea, vomiting, abdominal pain, and hyperkalemia. Literature reports have described successful use of digoxin immune fab in managing non-digoxin cardiac glycoside poisonings with oleander leaves [ 24 ], toad venom [ 25 ], and some Chinese herbal supplements [ 26 , 27 ]; others have reported unfavorable outcomes, including in cases of severe yew poisoning [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%